Citral effect in male NMRI mice nonalcoholic steatosis model: assessing biochemical and histological parameters and PPARα gene expression - Maryam Vaezi; Parichehreh Yaghmaei; Nasim Hayati-Roodbari; Shiva Irani; Azadeh Ebrahim-Habibi (Universidade de São Paulo, 2018)
Citral is a small molecule present in various citrus species, with reported anti-hyperlipidemic and anti-inflammation effects. Here, the effect of intraperitoneal (IP) administration of citral is evaluated in a mouse model of non-alcoholic steatosis. Male NMRI mice were divided into the following groups (n = 12): normal control group (NC) receiving a normal diet; high-fat emulsion group (HF) receiving high fat diet for four weeks; positive control group (C+) receiving HF diet for four weeks and then shifted to normal diet with IP-administered silymarin (80 mg/kg) for four weeks; sham group receiving HF diet for four weeks and then shifted to normal diet for four weeks; and EC1, EC2, and EC3 groups receiving HF diet for four weeks and then shifted to normal diet with IP-administered citral doses of 5, 10, and 20 mg/kg, respectively. HF diet resulted in steatohepatitis with impaired lipid profile, high glucose levels and insulin resistance, impaired liver enzymes, antioxidants, adiponectin and leptin levels, decreased PPARα level, and fibrosis in the liver tissue. Upon treatment with citral, improvement in condition was observed in a dose-dependent manner-both at histological level and in the serum of treated animals. and the PPARα level was also increased.